Design of mechanical arm based on piston fire rescue and emergency lock system in public places. (October 2019) - Ma, Yuan; Tang, Bo; Ma, Xu; Chen, Yuxiao; Wang, Yong; Zhang, Ziqi; Liu, Lu
Abstract: In recent years, emergency have occurred in public place, especially fire, such as the Xinyi City Yiyuan Song and Dance Hall in Liaoning, and the Karamay Friendship Hall in Xinjiang, Henan Jiaozuo City Paradise Audio and Video Club. The common lesson is that the security channel is blocked by the security door and the security net, and the security exit is closed, causing people to escape without a door when the fire occurs, causing heavy casualties. Again and again, firefighting and rescue, all must first remove the security door, iron fence window to rescue the trapped people, missed the best time to extinguish the fire. In order to solve the problem of unimpeded safety exits, it is necessary to solve the problem of consistency between normal use management and fire safety. It is difficult to be effective only by administrative means, and technical measures must be taken to solve the problem of safety dredging. Small-scale hotels, Internet cafes, etc. without fire or security systems must be able to push open the emergency exit door, but an alarm will be generated locally when the door is opened during normal working hours. The emergency exit door of an emergency gathering place such as a large-scale hotel, an Internet cafe, a dance hall, a hotel, a department store, etc., which is connected by a fire-fighting linkage system or an anti-theft alarm linkage system, must be pushed open, but will open when the door is opened during normal working hours. Local alarms are generated, so it is especially important to design a security door that can automatically unlock when an emergency occurs in a public place.